Liming applications and the SPAD chlorophyll index and stomatal conductance in cocoa exposed to cadmium in the soil - Suárez-Parra, Karen Victoria; Castañeda-Serrano, Cristian Santiago; Forero-Ulloa, Fabio Emilio; Almanza-Merchán, Pedro José; Serrano-Agudelo, Pablo César (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2022)
Cadmium is a heavy metal that affects cell structures, such as walls and membranes, especially in the photosynthetic apparatus (PSII), chlorophylls, chloroplasts and stomata, producing losses in production quantity and quality. In addition, it is harmful to the health of humans and animals. The objective was to analyze the behavior of the relative chlorophyll index (SPAD units) and stomatal conductance in clone CCN-51 cacao plants every 45 days (45, 90, 135 and 180 days) after liming application. Four doses of a dolomite + agricultural gypsum mixture were applied, increasing Ca+2 saturation in the soil to 7, 8 and 9 cmolc kg-1. The control treatment did not have applications. The results indicated a reduction in SPAD units in the plants without liming, with high cadmium levels in the soil (3.3 mg kg-1), and there were no statistical differences in the other treatments, possibly because of edaphic factors such as pH, organic matter content and Al+3. The best stomatal conductance was observed with 7 cmolc kg-1 in the foliar gas exchange. Supersaturated liming applications efficiently reduce the losses in quality and quantity caused by the accumulation of cadmium in cacao plants.